The puzzle of Latin American economic development - Patrice Franko, Colby College (Lanham Rowman & Littlefield Publishing Group, 2018)
Development in Latin America : conceptualizing economic change in the region -- Historical legacies : patterns of unequal and unstable growth -- Import substitution industrialization : looking inward for the source of economic growth -- Latin America's debt crisis : the limits of external financing -- Macroeconomic stabilization : a critical ingredient for sustained growth -- Public and private capital flows to Latin America -- Contemporary trade policy : engine or brakes for growth? -- Microeconomic foundations for growth and competitiveness in the global economy -- Latin American agriculture : achieving sustainable and equitable rural development -- Poverty in Latin America -- Health policy: investing in people's future -- Education : the source of equitable, sustainable growth -- Promoting sustainable environments in Latin America -- Lessons (not quite) learned : cycles in Latin American development -- Appendix: A sampling of institutional actors in Latin American economic policy -- Glossary -- Bibliography -- Index -- About the author.
Includes bibliographical references and index.
Keywords: Latin America--Economic conditions--1982-